A new species and some new records of leafhopper tribe Scaphoideini (Hemiptera: Cicadellidae: Deltocephalinae) from India - Rajgopal, N. N.; Meshram, Naresh M; Dey, Debjani (Zootaxa, 2022)
A new species of leafhopper, Scaphoideus banjarensis sp. nov. from India (Himachal Pradesh: Banjar), is described. Also two genera, Neolimnus Linnavuori and Wanritettix Vilbaste, and four species of tribe Scaphoideini, are newly reported from India: N. egyptiacus (Matsumura) and N. quadricornis Khatri & Webb; W. wanrianus (Matsumura); and Grammacephalus punjabensis Shah & Duan. Indian Scaphoideini currently comprises 78 species in 18 genera, including those newly reported here. Illustrations and distributions for newly recorded species are also included.